Estudo da conformação da β-Lactoglobulina em meio ácido na presença de íons de cálcio – sob aquecimento - Camargo, Leticia Vieira Emiliano (Universidade Federal do Tocantins, 2021)
β-lactoglobulin (β-1g), a globular protein considered small, has each monomer with 162 amino acids. Usually, at neutral pH and ambient temperature, it is in the form of dimers, native form - where each subunit has the molecular weight of approximately 18.3 kDa. In addition to temperature, the pH value and the calcium content are well known factors that influence the denaturation and aggregation of the whey protein. In this context, the present work aimed to study the changes in β-lactoglobulin (β-lg) structure caused by heating in the presence of calcium ions (Ca) in acid medium. Based on the conditions established during the experiments, it was possible to verify, through the Laser Diffraction (LD) granulometry, that the pH change and the heating modifies the particle size of the studied solutions. In the investigation by nuclear magnetic resonance (NMR) it was observed in low pHs the aggregation is smaller due to the temperatures used, so the phenomenon that stands out most is denaturation, especially in the samples in which they were previously heated.